I am trying to find $$\int \frac {\sqrt {x^2 - 4}}{x} dx$$

I make $x = 2 \sec\theta$

$$\int \frac {\sqrt {4(\sec^2 \theta - 1)}}{x} dx$$

$$\int \frac {\sqrt {4\tan^2 \theta}}{x} dx$$

$$\int \frac {2\tan \theta}{x} dx$$

From here I am not too sure what to do but I know I shouldn't have x.

$$\int \frac {2\tan \theta}{2 \sec\theta} dx$$

I also know I shouldn't have dx anymore.

$$dx = 2\sec \theta \tan \theta \; \mathrm d\theta$$

$$\int \frac {2\tan \theta}{2 \sec\theta} 2\sec \theta \tan \theta \; \mathrm d\theta$$

$$\int {2\tan^2 \theta} \; \mathrm d\theta$$

$$2\int {\tan^2 \theta} \; \mathrm d\theta$$

I have no idea how to find the integral of $\tan^2 \theta$

So I use Wolfram Alpha:

$$\tan \theta - \theta + c$$

Now I need to replace theta with x.

$$x = 2 \sec\theta$$

With same mathmagics I produce

$$ \frac {x}{2} = \sec \theta$$

$$ \theta = \operatorname {arcsec} \left(\frac{x}{2}\right)$$

$$\tan \left(\operatorname {arcsec} \left(\frac{x}{2}\right)\right) - \left(\operatorname {arcsec} \left(\frac{x}{2}\right)\right) + c$$

This is wrong but I am not sure why.

  • 3
    $\begingroup$ Congratulations Jordan, you're getting better at this! (But that is not magic, it is maths!) $\endgroup$ – Pedro Tamaroff Jun 4 '12 at 1:40

You are correct. First note that you have not carried a factor of $2$, since your integral is $2 \int \tan^2(\theta) d \theta$.

Hence your solution should read $$2 \tan(\text{arsec}(x/2)) - 2 \text{arcsec}(x/2) + c$$ You may want to rewrite your solution to match with the solution in your text. For instance, $$\text{arsec}(x/2)) = \arctan \left( \dfrac{\sqrt{x^2-4}}{2} \right)$$

So why is the above identity true? If we let $\text{arsec}(x/2)) = \theta$, then we get that $\sec(\theta) = x/2$ i.e. $\sec^2(\theta) = \dfrac{x^2}{4}$. We have that $\tan^2(\theta) = \sec^2(\theta) - 1 = \dfrac{x^2}{4} - 1 = \dfrac{x^2-4}{4}$ i.e. $\tan(\theta) = \dfrac{\sqrt{x^2 - 4}}{2}$. Hence, $$\theta = \arctan \left( \dfrac{\sqrt{x^2-4}}{2}\right)$$

Hence, we have the identity, $$\text{arsec}(x/2)) = \arctan \left( \dfrac{\sqrt{x^2-4}}{2} \right)$$

If you use this, then your solution will read $$\sqrt{x^2 - 4} - 2 \, \text{arsec}(x/2)) + c = \sqrt{x^2 - 4} - 2 \, \arctan \left( \dfrac{\sqrt{x^2-4}}{2} \right) + c$$


you're getting a lot better at these. In fact the answer you have is completely correct, it probably just doesn't look like the answer in the book. You get that with trig functions a lot, since there are often multiple ways of representing the same thing. What answer do you think you should have gotten?

EDIT: Okay. The term that looks different is $tan(arcsec(x/2))$. There are going to be a few heavy trig identities here:

$x=2\sec\theta=\frac 2 {\cos\theta}$, so $arcsec\frac x 2=\cos^{-1}\frac 2 x$. I'm doing this because I'm going to rewrite $\tan$ in terms of $\cos$ and cancel out $\cos(\cos^{-1}\frac 2 x)=\frac 2 x$ $$\tan(\cos^{-1}\frac 2 x)=\frac{\sin(\cos^{-1}\frac 2 x)}{\cos(\cos^{-1}\frac 2 x)}=\frac{\sqrt{1-(\cos(\cos^{-1}\frac 2 x))^2}}{\cos(\cos^{-1}\frac 2 x))^2}$$ $$=\frac{\sqrt{1-\frac 4 {x^2}}}{\frac 2 x}$$ $$=\frac{\sqrt{1-\frac 4 {x^2}}}{\frac 2 x}=\frac{x\sqrt{1-\frac 4 {x^2}}} 2=\frac{\sqrt{x^2-4}} 2$$

Which when multiplied by the $2$ on the outside of your integral gives the answer.

  • $\begingroup$ I am suppose to have $\sqrt{x^2 - 4} - 2sec^{-1}(\frac{x}{2} +c$ $\endgroup$ – toby yeats Jun 4 '12 at 1:34
  • $\begingroup$ How do you do x * $\sqrt{1 - \frac{4}{x^2}}$ $\endgroup$ – Jwan622 Feb 2 at 17:57

Multiply both top and bottom by $\sqrt{x^2 - 4}$ to obtain $$ \int\dfrac{x^2 - 4}{x\sqrt{x^2 - 4}}\,\mathrm{d}x=\int\dfrac{x}{\sqrt{x^2 - 4}} + 4\int-\dfrac{1}{x}\dfrac{1}{\sqrt{x^2\left(1 - (2/x)^2\right)}}\,\mathrm{d}x $$ In the fisrt integral, set $u=x^2-4$ and $x\,\mathrm{d}x = \dfrac{1}{2}\,\mathrm{d}u$ to get $$ \int\dfrac{x}{\sqrt{x^2-4}}\,\mathrm{d}x = \sqrt{x^2 - 4}+C_0. $$ In the second, consider $x>2$: $$ 2\int-\dfrac{2}{x^2}\dfrac{\mathrm{d}x}{\sqrt{1 - (2/x)^2}} $$ Now, set $u=\dfrac{2}{x}$ and $\mathrm{d}u = -\dfrac{2}{x^2}\,\mathrm{d}x$. Then, $$ \begin{aligned} 2\int-\dfrac{2}{x^2}\dfrac{\mathrm{d}x}{\sqrt{1 - (2/x)^2}} &=2\int\dfrac{\mathrm{d}u}{\sqrt{1 - u^2}} \\ &=2\arcsin u + C_1 \end{aligned} $$

Adding them up: $$ \int\dfrac{\sqrt{x^2 - 4}}{x}\,\mathrm{d}x = \sqrt{x^2 - 4} + 2\arcsin\left(\frac{2}{x}\right) + C $$

Note that, if $x<-2$, we would obtain the integral $$\int\dfrac{\sqrt{x^2 -4}}{x}\,\mathrm{d}x = \sqrt{x^2 - 4}-2\arcsin\left(\dfrac{2}{x}\right)+C, $$ but, since $x<-2$, $-2\arcsin\left(\dfrac{2}{x}\right)>0$, and the sign would become positive.

Therefore, we can write $$\begin{aligned} \int\dfrac{\sqrt{x^2 - 4}}{x}\,\mathrm{d}x &= \sqrt{x^2-4}+2\arcsin\left(\dfrac{2}{|x|}\right) + C \\&= \sqrt{x^2-4}+2\operatorname{arccsc}\left(\dfrac{|x|}{2}\right) + C \end{aligned} $$

Note that the arbitrary constants are not necessarily the same.


Another answer to this question probably isn't necessary. This post is really just an excuse to introduce a technique I wish someone had taught me in high-school.

Suppose $x>2$. Substitute $\sqrt{x^2-4}=(x-2)t$. This is the third substitution of Euler. Note that we have $t>1$. Solving for $x$ in the substitution relation, we have $x=\frac{2(t^2+1)}{t^2-1}\implies\mathrm{d}x=-\frac{8t}{(t^2-1)^2}\,\mathrm{d}t$. This transforms the integrand to a rational function of $t$:


Expanding via partial fractions,


Hence, the integral has been reduced to three elementary integrals, and we've done it without the usual machinery of trigonometric substitutions.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.